Dynamic Gains from Trade The Role of Intermediate Inputs and Equipment Imports - Stone, Susan (OECD Trade Policy Papers, 2011)
Dynamic gains from trade can be an important conduit for increased firm-level innovation and productivity, both key components of economic growth. This paper builds on previous research on the dynamic gains from trade by moving beyond a single country basis to examine impacts on firm-level productivity for a cross-section of countries. It also focuses on productivity gains through the import of intermediate inputs and capital goods and systematically explores the specific impacts of non-trade, or complementary, policies on firms' ability to realise dynamic gains. This paper shows that a range of complementary policies affects a firm's ability to generate productivity gains from intermediate and capital goods imports. Access to skilled labour is a particularly important policy variable with respect to the import of intermediate goods, followed by access to finance, while macroeconomic stability slightly outranks access to finance for capital goods importers. The importance of access to finance has particular policy significance given the wide-spread financial reforms being discussed or underway